Development of FexOy particle onto bacterial cellulose network by forced hydrolysis and its electrical conductivity - KHAMWONGSA, Prompong; WONGJOM, Poramed; MUCHLISC, Andi Magattang Gafur; LIN, Chun Che; SRISUK, Seranee; UMMARTYOTIN, Sarute (Journal of Metals, Materials and Minerals, 2022)
FexOy particle and bacterial cellulose composite sheet was successfully prepared by forced hydrolysis. The presence of Fe3+ ions in bacterial cellulose suspension significantly provided the positive charge due to electrostatic force as reported by Zeta potential. With the pH of 12 of bacterial cellulose suspension, particle was nucleated between bacterial cellulose networks. Fourier transform infrared exhibited Fe-O stretching. X-ray diffraction reported that the mixture of Fe2O3 and Fe3O4 was existed onto bacterial cellulose composite. Scanning electron microscope reported that FexOy particle was randomly distributed in bacterial cellulose network. Intensity of Fe was qualitatively observed by energy dispersive analysis. With the existence of FexOy particle, the composite illustrated the inferiority of thermal stability of 150℃. Furthermore, it was noted that the resistivity was reduced with respect to increment of FexOy particle, suggesting that electrical conductivity was then enhanced. It was remarkable to note that FexOy particle and bacterial cellulose composite sheet prepared from forced hydrolysis showed the excellent properties as a candidate for flexible electrode.